Bone grafting of alveolar socket and ovate seat pontic preparation for natural emergence profile for anterior bridge - A case report - Vijay Deshmukh; Kamlesh P Talesara; Amrita Kishore (Wolters Kluwer Medknow Publications, 2009)
Alveolar atrophy following tooth extraction remains a challenge for future prosthetic restorations. Immediate implant placement and postextraction alveolar bone grafting are two methods that are used to prevent significant postextraction bone loss. Grafting is one of the most common methods of socket preservation widely used to prevent the collapse of oral tissues following extraction so that an excellent esthetic prosthesis can be provided particularly in the anterior maxillary region. The present report describes the management of a maxillary tooth extraction socket using a socket preservation technique involving placement of an osteoconductive slowly resorbable grafting material & resorbable collagen membrane in the extraction socket also called as Bio-Col socket preservation technique followed by a provisional restoration to preserve the tissues & interdental papilla for the placement of future final ovate pontic anterior bridge to give the illusion of the tooth emerging from the gums. This technique resulted in a successful prevention of alveolar bone loss following tooth extraction & maintainence of tissue contour & density which provided a good tissue base for the fabrication of Ovate pontic giving excellent esthetic results.